2021
DOI: 10.3390/met11122037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residual Stresses on the Fatigue Lifetimes of Self-Piercing Riveted Joints of AZ31 Mg Alloy and Al5052 Al Alloy Sheets

Abstract: During the self-piercing riveting (SPR) process, residual stress develops due to the high plastic deformation of the sheet materials. In this study, the effect of the residual stress on the fatigue lifetime of SPR joints with dissimilar magnesium AZ31 alloy and aluminum Al5052 alloy sheets was evaluated. The residual stress distribution was derived through a simulation of the SPR process by the FEA (finite element analysis). The measured values by the X-ray diffraction technique confirmed that the validity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Zhang et al [23,24] reported the fatigue property, crack growth mechanism, and performance of TA1 self-piercing riveted joints. Lee et al [25] found that the fatigue life was related to the amplitude of stress, and the smaller the amplitude of stress, the longer the fatigue life. Presse et al [26] studied the fatigue life of different combination SPR joints according to the stress-life curve.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [23,24] reported the fatigue property, crack growth mechanism, and performance of TA1 self-piercing riveted joints. Lee et al [25] found that the fatigue life was related to the amplitude of stress, and the smaller the amplitude of stress, the longer the fatigue life. Presse et al [26] studied the fatigue life of different combination SPR joints according to the stress-life curve.…”
Section: Introductionmentioning
confidence: 99%
“…22 At present, the method of evaluating the quality of riveting is mainly used through the tolerance band method of the force-displacement curve. 23 However, the tolerance band formed by the upward and downward displacement of the qualified joint force-displacement reference curve is not only insensitive to lateral displacement, but also cannot monitor rivet offset, button cracking, and joint cracking. Furthermore, there is a certain detection blind spot in the tolerance band.…”
Section: Introductionmentioning
confidence: 99%